Cross over from 3D variable range hopping to the 2D weak localization conduction mechanism in disordered carbon with the extent of graphitization - Raj, Kovummal Govind; Joy, Pattayil Alias (Physical Chemistry Chemical Physics, 2015)
The changes in the electrical transport properties and mechanism of conduction in disordered carbon, with the extent of graphitization, are studied and discussed. With heat treatment induced graphitic ordering, the electrical properties are considerably modified, inducing a crossover from strong localization to weak localization behavior. Accordingly, the conduction mechanism is modified from the 3-dimensional variable range hopping (3D VRH) model to the 2-dimensional weak localization (2D WL) model. Results show that carrier-carrier and carrier-phonon interactions play major roles in developing the weak localization behavior with the extent of graphitization.